202k views
2 votes
Log x = log(x + 3) - log(x - 1)

User Nowox
by
4.8k points

2 Answers

3 votes

Please find attached photograph for your answer.

Log x = log(x + 3) - log(x - 1)-example-1
User Chris Herring
by
4.7k points
1 vote

First note that log(x) is defined only for x > 0; log(x + 3) for x > -3; and log(x - 1) for x > 1. So if we find any solutions x ≤ 1, these will be extraneous.

Condense the right side:

log(x) = log((x + 3) / (x - 1))

Let b be the base of the logarithm. Then writing both sides as powers of this b simplifies the equation to

b^log(x) = b^log((x + 3) / (x - 1))

x = (x + 3) / (x - 1)

Solve for x :

x (x - 1) = x + 3

x ² - x = x + 3

x ² - 2x - 3 = 0

(x - 3) (x + 1) = 0

x - 3 = 0 or x + 1 = 0

x = 3 or x = -1

We throw out x = -1 because it's less than 1, so the only (real) solution is x = 3.

User Julime
by
5.2k points